ANALISIS KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN METODE DUPONT PADA PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2022-2024 - Pajar Anugrah; Ardi Hirmansah; Rina Malahayati (CV. Armas Suan Sejahtera, 2025)
This study analyzes the influence of Net Profit Margin (NPM), Total Asset Turnover (TATO), and Equity Multiplier (EM) on Return on Equity (ROE) across 13 companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This timeframe is crucial for capturing the post-pandemic recovery dynamics marked by inflation and rising interest rates. The analytical method employed was panel data regression using the Fixed Effect Model (FEM). The findings indicate that simultaneously, NPM, TATO, and EM have a significant influence on ROE, with the model explaining approximately 78.5% of the ROE variation. Partially, NPM and TATO were both found to have a positive and significant effect on ROE. This confirms that operational efficiency (NPM) in managing costs and asset utilization efficiency (TATO) in generating sales are fundamental factors for boosting equity profitability. However, the Equity Multiplier (EM) showed a positive coefficient but was not statistically significant (p-value 0.084, above the 5% threshold) toward ROE. The insignificance of EM is interpreted as a potential result of increased debt costs due to rising interest rates, which could neutralize the positive effects of leverage. The implications of this study highlight the need for company management to focus on operational strengths and asset efficiency as the key sustainable drivers of ROE